2011
DOI: 10.3182/20110828-6-it-1002.00274
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Control for Multi-Robot Observation of Multiple Moving Targets Based on Discrete-Continuous Linear Models

Abstract: The observation of multiple moving targets by cooperating mobile robots is a key problem in many security, surveillance and service applications. In essence, this problem is characterized by a tight coupling of target allocation and continuous trajectory planning. Optimal control of the multi-robot system generally neither permits to neglect physical motion dynamics nor to decouple or successively process target assignment and trajectory planning. In this paper, a numerically robust and stable model-predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The approach presented in this paper can be seen as a starting point towards such a distributed application: While the authors already presented a possible distributed variant of the cooperative controller (Kuhn et al, 2011), the decentralization of simulation, estimation and observation point generation is subject of active research.…”
Section: Resultsmentioning
confidence: 99%
“…The approach presented in this paper can be seen as a starting point towards such a distributed application: While the authors already presented a possible distributed variant of the cooperative controller (Kuhn et al, 2011), the decentralization of simulation, estimation and observation point generation is subject of active research.…”
Section: Resultsmentioning
confidence: 99%
“…Robot formation [65] Model-predictive control C [66] Clustering Dc [67] Integer linear program C [68], [ [78] Negotiation and auctions D…”
Section: Problem Formulationmentioning
confidence: 99%
“…More recent work on the CMOMMT problem has shown that simultaneous optimization of discrete target assignments and robot motion improves the team performance (Kuhn et al., ). The optimization of assignments and robot motions was found using an exact MILP solver, which scales exponentially in the number of robots and targets.…”
Section: Related Workmentioning
confidence: 99%